Pengaruh Pelatihan Terhadap Pengetahuan tentang Gizi Buruk dan Inter-Professional Collaboration Petugas Puskesmas - Eny Pemilu Kusparlina (FORUM ILMIAH KESEHATAN, 2021)
The problem of nutritional status is very complex, requiring treatment involving a health nutritionist. The nutritional status of children is one of the important things to prepare a quality generation. Health education in the form of training is expected to be able to change the collaborative competences of health workers across professions. This study aims to analyze the effect of training on knowledge of health workers about malnutrition and cross-professional collaboration. The researcher used a mix-methods approach with triangulation techniques using a questionnaire for the qualitative stage by conducting content analysis, while in the quantitative stage the researcher used a pre-experimental design with a